Oxygen reservoir effect of Tungsten trioxide electrode on endurance performance of ferroelectric capacitors for FeRAM applications - Yejoo Choi; Jaemin Shin; Jinhong Min; Seungjun Moon; Daeyoung Chu; Donghwan Han; Changhwan Shin (Scientific Reports)
Abstract The effect of W and WO3 electrodes on the ferroelectric characteristics of HZO (Zr-doped HfO2)-based MFM (metal-ferroelectric-metal) capacitors was investigated. During the deposition of tungsten, the W electrode was formed using only Ar gas, while the WO3 electrode was formed using a mixture of Ar and O2 gases. The W-based MFM capacitors exhibited superior remnant polarization (2Pr of 107.9 µC/cm2 at 700 oC) compared to the WO3-based capacitors; however, their endurance performance was degraded. In contrast, the WO3-based capacitors showed endurance performance enhanced by three orders of magnitude due to the oxygen-rich reservoir effect. The oxygen introduced during the deposition of WO3 prevented the oxygen scavenging effect of tungsten. Consequently, excessive generation of oxygen vacancies in the HZO layer was suppressed, resulting in improved endurance performance. These results were quantitatively confirmed through TEM, XPS, and XRD analyses.